«Trilce» as an interpretation of the real: subtractive procedure and location of the object a - Mondoñedo Murillo, Marcos (2023)
This paper raises the possibility of understanding the poem «Trilce», by César Vallejo, as a discourse that contains specifically psychoanalytical analytical operations. The fact that it is external to the collection of poems of the same name and the rhetorical and thematic operations that compose it allow us to observe that this poem is organised, in an anticipatory way, with a logic that is pertinent to Lacanian-oriented discourse analysis. This logic involves incorporating into the field of signification that which does not cease to be incorporated into it, that is, what in Lacanian terms is the real. In this case, that which has the structure of a presence whose subtraction becomes the absent cause around which all the signification of the discourse concerned revolves: what Lacan calls the object a.